THE EXPLORATION OF THE MEDIA’S INFLUENCE ON THE FEAR OF CRIME IN PAKISTAN - Nasir Khan; Akhtar Ali; Murtaza Bashir Dar (International Journal of Contemporary Issues in Social Sciences, 2024)
This study attempts to elucidate the influence of media on the perception of crime-related apprehension using a sample from Pakistan. In particular, this study explores how people interpret media and how that interpretation affects their contextual fear of crime. The aim of this study is to determine if variables like home location (rural versus urban) and certain socio-demographic traits are significant in how people understand media information related to insecurity. Ten of the participants in the fifteen structured interviews were from rural areas, and five were from metropolitan areas. One of the most notable conclusions is that it is difficult to uncover a clear link between media intake and insecurities. Instead, a multitude of interpretations surface, making the media’s impact on the fear of crime unpredictable. This analysis reveals that a number of factors, including sensationalism, temporal proximity to the occurrence, the practicality of news coverage, and geographic immediacy to reported crimes, are important variables. Essentially, this study highlights the value of qualitative research in examining this thematic domain through experiential and discursive lenses by providing a complex knowledge of insecurity that is obtained from a variety of viewpoints and approaches.